2016
DOI: 10.3892/ijmm.2016.2451
|View full text |Cite
|
Sign up to set email alerts
|

A deficiency in cold-inducible RNA-binding protein accelerates the inflammation phase and improves wound healing

Abstract: Chronic or non-healing wounds are a major concern in clinical practice and these wounds are mostly associated with diabetes, and venous and pressure ulcers. Wound healing is a complex process involving overlapping phases and the primary phase in this complex cascade is the inflammatory state. While inflammation is necessary for wound healing, a prolonged inflammatory phase leads to impaired healing. Cold-inducible RNA-binding protein (CIRP) belongs to a family of cold-shock proteins that are expressed in high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 33 publications
4
19
0
Order By: Relevance
“…Sufferers of other inflammation‐related disorders, such as abdominal aortic aneurysm are also advised to use anti‐CIRP therapies based on animal experiments . Furthermore, CIRP deficiency could also accelerate the inflammation phase and wound healing process . Taken together, these results strongly suggested that extracellular CIRP, as a novel proinflammatory molecule, induces inflammatory responses leading tissue injury (Fig.…”
Section: Action Of Cirp As a Novel Damp In Inflammatory Responsementioning
confidence: 90%
“…Sufferers of other inflammation‐related disorders, such as abdominal aortic aneurysm are also advised to use anti‐CIRP therapies based on animal experiments . Furthermore, CIRP deficiency could also accelerate the inflammation phase and wound healing process . Taken together, these results strongly suggested that extracellular CIRP, as a novel proinflammatory molecule, induces inflammatory responses leading tissue injury (Fig.…”
Section: Action Of Cirp As a Novel Damp In Inflammatory Responsementioning
confidence: 90%
“…Pretreatment of donor nerve allografts with cold preservation decreases immunosuppression requirements and has been used in the clinical setting to reduce nerve allograft rejection (Grand, Myckatyn, Mackinnon, & Hunter, ). Furthermore, CIRP deficiency accelerates the inflammation phase and wound healing process (Idrovo et al, ). All of these reports indicated that reduced immune rejection occurs due to appropriate pretreatment and cryopreservation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the quantitative measurement of CIRP levels in peripheral blood using an ELISA kit appears achievable, opening the possibility to investigate CIRP as a new diagnostic marker for sepsis [ 130 ]. Furthermore, CIRP deficiency accelerates inflammation phase and wound healing process [ 131 ]. Overall, extracellular CIRP induces cell damage by inducing inflammatory responses.…”
Section: Regulation and Functions Of Cirpmentioning
confidence: 99%